Knowledge and Attitude of Health Science Students Towards Epilepsy in a Nigerian University (African Journal of Biomedical Research, 2019)
Behaviour of people, especially health workers, towards people living with epilepsy (PLE) represents an important public health concern. This study explores knowledge and attitude of health science undergraduates of a Nigerian University towards PLE using a cross-sectional survey involving consecutively 656 (52.7% males; 47.3% females) undergraduates. The Epilepsy Knowledge Questionnaire (EKQ) and the Attitude towards Persons with Epilepsy (ATPE) rating scale were used to collect data on the participants’ knowledge and attitude towards PLE respectively. Data was analyzed using descriptive statistics, Spearman rank, Mann-Whitney U and Kruskal-Wallis tests at 0.05 alpha level. The mean knowledge and attitude towards epilepsy was moderate and good respectively. Majority of the participants had fair knowledge (64.3%) and good attitude (70.3%). Knowledge of the participants about epilepsy had positive significant correlations with their age and year of study and was significantly influenced by their age, faculty, department and year of study. Participants’ attitude towards PLE neither correlated nor was influenced by any of the aforementioned variables (p>0.05). Knowledge and attitude of the participants towards epilepsy did not significantly correlate with each other (p>0.05). Knowledge of Nigerian students about epilepsy is poor which is associated with their age, level of study, faculty and department of study. The attitude of the students towards PLE was good and did not correlate or influenced by any of their characteristics. There is need to improve the knowledge of health science students about epilepsy